Development of a smart insole for medical and sports purposes - Tan, A. M.; Fuss, F. K.; Weizman, Y.; Troynikov, O. (Procedia Engineering, 2015)
A study was conducted to determine the performance of a low cost plantar measuring device. The aim of the device was to establish an in-shoe measurement system with high resolution and to take relatively accurate measurements. The calibration method for the smart material was established with the use of a Kistler force plate. The coefficient of determination r2 of the force against resistance calibration curve was 0.974. The residual standard deviation amounted to 13.91 N. The r2 value of the repetitive loading experiments amounted to 0.981. The residual standard deviation was 70.35 N for forces larger than 700 N. From the data obtained, the insole is deemed to be sufficiently accurate for quantitative analysis.